Protein–ligand binding affinity prediction of cyclin‐dependent kinase‐2 inhibitors by dynamically averaged fragment molecular orbital‐based interaction energy. Issue 20 (9th June 2022) - Takaba, Kenichiro; Watanabe, Chiduru; Tokuhisa, Atsushi; Akinaga, Yoshinobu; Ma, Biao; Kanada, Ryo; Araki, Mitsugu; Okuno, Yasushi; Kawashima, Yusuke; Moriwaki, Hirotomo; Kawashita, Norihito; Honma, Teruki; et al.
Abstract: Fragment molecular orbital (FMO) method is a powerful computational tool for structure‐based drug design, in which protein–ligand interactions can be described by the inter‐fragment interaction energy (IFIE) and its pair interaction energy decomposition analysis (PIEDA). Here, we introduced a dynamically averaged (DA) FMO‐based approach in which molecular dynamics simulations were used to generate multiple protein–ligand complex structures for FMO calculations. To assess this approach, we examined the correlation between the experimental binding free energies and DA‐IFIEs of six CDK2 inhibitors whose net charges are zero. The correlation between the experimental binding free energies and snapshot IFIEs for X‐ray crystal structures was R 2 = 0.75. Using the DA‐IFIEs, the correlation significantly improved to 0.99. When an additional CDK2 inhibitor with net charge of −1 was added, the DA FMO‐based scheme with the dispersion energies still achieved R 2 = 0.99, whereas R 2 decreased to 0.32 employing all the energy terms of PIEDA. Abstract : Experimental binding free energies of CDK2 inhibitors were compared with the binding energies by DA‐FMO‐based approach in which MD simulations were used to generate multiple protein–ligand complex structures. For six CDK2 inhibitors with zero charges, the DA‐FMO‐based interaction energies of the protein–ligand complexes showed higher correlations with the experimental values than those calculated with the X‐ray crystal structure. The dispersion term of DA‐FMO‐based interaction energies retained the high correlation even including a charged ligand.